IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA PADA PEMBELAJARAN IPAS KELAS V SDN 5 CAKRANEGARA - Rizaldi, Imam; Sukri, Sukri; Amrullah, Lalu Wira Zain; Makki, Muhammad (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to describe the planning, implementation, and evaluation of the implementation of differentiated learning in the Merdeka Curriculum in fifth grade science learning at SDN 5 Cakranegara, Mataram. Using a descriptive qualitative approach, data were collected from fifth grade teachers through interviews, observations, and documentation. Data analysis applied the Miles and Huberman model including data reduction, data presentation, and drawing conclusions. The results of the study showed that the planning stage included diagnostic assessments to map student learning profiles, analysis of learning outcomes, and design of differentiated teaching strategies and tools with technology support. At the implementation stage, teachers act as facilitators and motivators, provide individual/group guidance, and apply differentiation to content, processes (methods/media), and products (final results) according to student characteristics and abilities. Learning evaluation is carried out through continuous reflection and analysis for improvement. It was concluded that the implementation of differentiated learning in this school went quite well, proven to be useful in meeting the needs of diverse students, increasing motivation, and learning outcomes. However, challenges were found such as limited teacher time in preparation and the need to develop the use of more varied learning media. ABSTRAKPenelitian ini bertujuan mendeskripsikan perencanaan, pelaksanaan, dan evaluasi implementasi pembelajaran berdiferensiasi dalam Kurikulum Merdeka pada pembelajaran IPAS kelas V di SDN 5 Cakranegara, Mataram. Menggunakan pendekatan kualitatif deskriptif, data dikumpulkan dari guru kelas V melalui wawancara, observasi, dan dokumentasi. Analisis data menerapkan model Miles dan Huberman meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan tahap perencanaan mencakup asesmen diagnostik untuk memetakan profil belajar siswa, analisis capaian pembelajaran, serta perancangan strategi dan perangkat ajar berdiferensiasi dengan dukungan teknologi. Pada tahap pelaksanaan, guru berperan sebagai fasilitator dan motivator, memberikan bimbingan individual/kelompok, serta menerapkan diferensiasi pada konten, proses (metode/media), dan produk (hasil akhir) sesuai karakteristik serta kemampuan siswa. Evaluasi pembelajaran dilakukan melalui refleksi dan analisis berkelanjutan untuk perbaikan. Disimpulkan implementasi pembelajaran berdiferensiasi di sekolah ini berjalan cukup baik, terbukti bermanfaat memenuhi kebutuhan beragam siswa, meningkatkan motivasi, dan hasil belajar. Meskipun demikian, ditemukan tantangan seperti keterbatasan waktu guru dalam persiapan dan perlunya pengembangan pemanfaatan media pembelajaran yang lebih variatif.